(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: A group encompassing a wide variety of lesions related to the disorder of vascular development, remain both diagnostic and treatment challenges to treating physicians. The terminology used to describe and classify vascular anomalies is the key for proper diagnosis and treatment. The classification system established by the International Society for the Study of Vascular Anomalies (ISSVA). is now a widely accepted system used to categorize vascular anomalies into two types: (1). vasoproliferative or vascular neoplasms such as hemangioma, and (2). vascular malformations. Vascular malformations, on the other hand, are comprised of abnormally formed channels within a vascular apparatus that are lined by endothelial cells and do not undergo abnormal cellular turnover. They too are congenital in nature, but often go unnoticed at birth, never regress, and grow proportionally with the individual. While most PWSs show a sporadic inheritance pattern, there is a number of associated congenital syndromes in which they manifest greater diffusion in addition to bone hypertrophy such as in Klippel-Trenaunay syndrome (KTS). or neurological involvement, as seen in the Sturge Weber Syndrome (SWS). Initially, PWSs clinically appear as fat pink or bright red hued patches. Although they may lighten during the first few months of life, probably due to the physiological anemia of infancy, this phenomenon is not predictive of a spontaneous regression of the vascular stain. Unlike other types of vascular birthmark, port wine stain do not fade with age. Initially a light pink to red macule at birth, the natural progression of port wine stain is to a deeper reddish-purple lesion that may become hypertrophic or nodular due to progressive vessel ectasia. In addition, the aberrant cosmetic appearance of PWS may significantly impede the patient’s psychosocial development and well-being, and because 70% to 80% of these birthmarks occur in the head and neck regions, many patients seek treatment.